2014
DOI: 10.1016/j.ijhydene.2014.03.228
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary results of the feasibility of hydrogen detection by the use of uncoated silicon microcantilever-based sensors

Abstract: International audienceHydrogen is a key parameter to monitor radioactive disposal facility such as the envisioned French geological repository for nuclear wastes. The use of microcantilevers as chemical sensors usually involves a sensitive layer whose purpose is to selectively sorb the analyte of interest. The sorbed substance can then be detected by monitoring either the resonant frequency shift (dynamic mode) or the quasi-static deflection (static mode). The objective of this paper is to demonstrate the feas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…The Euler-Bernoulli equation taking into account the hydrodynamic force acting on the uncoated microcantilever is commonly used to model the behavior of resonating microcantilevers in fluid media when the influence of the beam's shearing deformation and rotational inertia can be neglected [8] and [12]. Fig.…”
Section: Modelingmentioning
confidence: 99%
See 2 more Smart Citations
“…The Euler-Bernoulli equation taking into account the hydrodynamic force acting on the uncoated microcantilever is commonly used to model the behavior of resonating microcantilevers in fluid media when the influence of the beam's shearing deformation and rotational inertia can be neglected [8] and [12]. Fig.…”
Section: Modelingmentioning
confidence: 99%
“…With a view towards chemical detection in gas media, the variation of the gas density can reflect the variation of a chemical species concentration in a gas mixture [8,[12][13][14]. The operating principle of an uncoated silicon microcantilever (USMC) used as a density or chemical sensor is based on the influence of the mass of the fluid moved by the vibrating cantilever on the resonant frequency.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it has been shown that using a sensitive coating compromises the long term stability of the sensor (Korotcenkov and Cho, 2011) mostly due to aging of such film (Sharma et al, 2001;Romain and Nicolas, 2010). For this reason, there is an increasing interest toward uncoated sensors, which rely on the change of the physical properties of their surrounding gas such as thermal conductivity (Daynes, 1933;Hale et al, 1992;Simon and Arndt, 2002), or mass density (Tétin et al, 2010;Boudjiet et al, 2014;Rosario and Mutharasan, 2014). Despite the lack of selectivity of uncoated sensors, it is still possible to discriminate from different gases by measuring multiple parameters at once (Iglesias et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…This has been used previously for characterizing liquids (Heinisch et al, 2015) and even gases, despite the fact that their mass density and viscosity are much smaller. Gas detection such as hydrogen, carbon dioxide, argon, helium and methane detection have already been demonstrated using uncoated resonant sensors (Tétin et al, 2010;Boudjiet et al, 2014;Rosario and Mutharasan, 2014;Iglesias et al, 2019). These measurements have been performed either using silicon or piezoelectric cantilevers at frequencies below 200 kHz.…”
Section: Introductionmentioning
confidence: 99%